2007
DOI: 10.2139/ssrn.616761
|View full text |Cite
|
Sign up to set email alerts
|

Consumer and Competitor Reactions: Evidence from a Field Experiment

Abstract: In response to a price change by a single seller, it is common for the density of sellers in the market to influence both the quantity response of consumers and the price response of other sellers. Using field experiment data collected around a series of exogenously imposed price changes we find that an individual retailer with a larger number of competitors faces a more-responsive demand. This finding is fundamental to a predicted inverse relationship between market prices and the number of competitors. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Attempts to formally estimate the dynamic pricing strategies of individual gasoline retailers have been limited, perhaps because of data requirement. Barron et al. (2008) use a unique opportunity to impose exogenous price changes on stations of a firm in certain Californian areas to estimate the reactions of competitors.…”
Section: Studies Of Retail Gasoline Price Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to formally estimate the dynamic pricing strategies of individual gasoline retailers have been limited, perhaps because of data requirement. Barron et al. (2008) use a unique opportunity to impose exogenous price changes on stations of a firm in certain Californian areas to estimate the reactions of competitors.…”
Section: Studies Of Retail Gasoline Price Dynamicsmentioning
confidence: 99%
“… In another example of firm co‐operation, Barron et al. (2008) were given the opportunity to impose exogenous price changes on stations of a major retailer in certain California cities over a 3‐month period. …”
mentioning
confidence: 99%
“…The empirical evidence is far more supportive of Hotelling–Lancaster than of Spence–Dixit–Stiglitz. Barron et al (2008) compute price elasticities in U.S. gasoline markets and find that larger markets are associated with more elastic demand; Hummels and Lugovskyy (2008) document that import demand in larger markets is more responsive to changes in trade costs; Tybout (2003), in reviewing the literature on trade liberalization, concludes that markups fall with import competition; Campbell and Hopenhayn (2005) report a positive relationship between market size and firm size for a number of retail industries across U.S. cities; and Hummels and Klenow (2005) find that the number of varities increases less than proportionally with the size of the market across a wide variety of industries and countries 7 . Although others, such as Hummels and Klenow (2005) and Hummels and Lugovskyy (2008), have made the point that the Hotelling–Lancaster construct is more consistent with certain empirical regularities, we are the first to consider its relevance for technological innovation.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to local competition, studies have found ambiguous relations between station density and price. On the one hand, Barron et al (2004), Barron et al (2008) and Clemenz and Gugler (2006) show that higher station density tends to lower average prices, suggesting that a higher number of sellers raises local competition. This is in line with our findings, which 5 See Bresnahan (1989) for a discussion of this model.…”
Section: Sources Of Market Power In Gasoline Retailingmentioning
confidence: 99%